2007
DOI: 10.1002/hep.21561
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a double-blind, placebo-controlled trial of the antifibrotic efficacy of interferon-γ1b in chronic hepatitis C patients with advanced fibrosis or cirrhosis

Abstract: Interferon-␥1b (IFN-␥1b) is a pleiotropic cytokine that displays antifibrotic, antiviral, and antiproliferative activity. A total of 502 patients with compensated liver disease and an Ishak fibrosis score of 4-6 were randomized in a double-blind, placebo-controlled study, and 488 of these patients received subcutaneous injections of IFN-␥1b 100 g (group 1, n ‫؍‬ 169), IFN-␥1b 200 g (group 2, n ‫؍‬ 157), or placebo (group 3, n ‫؍‬ 162) 3 times a week for 48 weeks. Most patients (83.6%) had cirrhosis at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 30 publications
2
57
0
2
Order By: Relevance
“…28 A total of 502 patients met entry criteria and were randomized, and 488 received at least one dose of the study drug. Of those, 162 received placebo, 169 received 100 g IFN-␥ 1b 3 times weekly, and 157 received 200 g IFN-␥ 1b 3 times weekly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 A total of 502 patients met entry criteria and were randomized, and 488 received at least one dose of the study drug. Of those, 162 received placebo, 169 received 100 g IFN-␥ 1b 3 times weekly, and 157 received 200 g IFN-␥ 1b 3 times weekly.…”
Section: Resultsmentioning
confidence: 99%
“…28 Patients recruited into the study had clinically compensated chronic hepatitis C refractory to standard IFN-␣-based therapy, and they were required to have an adequate liver biopsy, evaluated by the central pathologist (Z.G. ), showing marked bridging fibrosis or cirrhosis, stages 4 to 6 of the Ishak score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…216 Based on this lesson, it is clear that trials in such cirrhotic patients will need to be lengthy, with the use of more sensitive and specific biomarkers that do not rely on biopsy alone. 217 Further progress in understanding, diagnosing, and treating hepatic fibrosis will continue to rely on the exploration of fundamental mechanisms of fibrogenesis, which is certain to lead to a meaningful impact on the prognosis of patients with chronic liver disease. Contributions of activated stellate cells and other fibrogenic cell types to hepatic fibrosis.…”
Section: Clinical and Translational Implicationsmentioning
confidence: 99%
“…18,23,24 Furthermore, treatment with IFN-γ was shown to ameliorate liver fibrosis in patients with hepatitis B viral or HCV infection, 25,26 but a recent clinical trial showed that IFN-γ treatment had no beneficial effect in patients with advanced liver disease. 27 The difference between these studies may be due to the selection of patients with differing stages of liver disease. It is possible that IFN-γ may have beneficial effects when treating early stages of liver fibrosis but not the later stage of cirrhosis.…”
mentioning
confidence: 99%